Decoding the intricacies: a comprehensive analysis of microRNAs in the pathogenesis, diagnosis, prognosis and therapeutic strategies for COVID-19 - Smail, Shukur Wasman; Hirmiz, Sarah Mousa; Ahmed, Akhter Ahmed; Albarzinji, Niaz; Awla, Harem Khdir; Amin, Kawa; Janson, Christer (Frontiers in Medicine, 2024)
The pandemic of coronavirus disease-19 (COVID-19), provoked by the appearance of a novel coronavirus named severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), required a worldwide healthcare emergency. This has elicited an immediate need for accelerated research into its mechanisms of disease, criteria for diagnosis, methods for forecasting outcomes, and treatment approaches. microRNAs (miRNAs), are diminutive RNA molecules, that are non-coding and participate in gene expression regulation post-transcriptionally, having an important participation in regulating immune processes. miRNAs have granted substantial interest in their impact on viral replication, cell proliferation, and modulation of how the host’s immune system responds. This narrative review delves into host miRNAs’ multifaceted roles within the COVID-19 context, highlighting their involvement in disease progression, diagnostics, and prognostics aspects, given their stability in biological fluids and varied expression profiles when responding to an infection. Additionally, we discuss complicated interactions between SARS-CoV-2 and host cellular machinery facilitated by host miRNAs revealing how dysregulation of host miRNA expression profiles advances viral replication, immune evasion, and inflammatory responses. Furthermore, it investigates the potential of host miRNAs as therapeutic agents, whether synthetic or naturally occurring, which could be harnessed to either mitigate harmful inflammation or enhance antiviral responses. However, searching more deeply is needed to clarify how host’s miRNAs are involved in pathogenesis of COVID-19, its diagnosis processes, prognostic assessments, and treatment approaches for patients.